Предмет: Математика,
автор: полинашка
2(x-4)=1
(X+1)+(X+3)=5
(6+2X)+ X=9
Ответы
Автор ответа:
0
2Х-8=1
2Х=1+8
2Х=9
Х=9:2
Х=4,5
Х+1+Х+3=5
2Х=5-1-3
2Х=1
Х=1:2
Х=0,5
6+2Х+Х=9
3Х=9-6
3Х=3
Х=3:3
Х=1
2Х=1+8
2Х=9
Х=9:2
Х=4,5
Х+1+Х+3=5
2Х=5-1-3
2Х=1
Х=1:2
Х=0,5
6+2Х+Х=9
3Х=9-6
3Х=3
Х=3:3
Х=1
Автор ответа:
0
2(х-4)=1
2х-8=1
2х=1-8
2х=-7
х=-7:2
х=3 12
(х+1)+(х+3)=5
х+1+х+3=5
2х=5-3-1
2х=1
х=12
(6+2х)+х=9
6+2х+х=9
3х=15
х=15:3
х=5
2х-8=1
2х=1-8
2х=-7
х=-7:2
х=3 12
(х+1)+(х+3)=5
х+1+х+3=5
2х=5-3-1
2х=1
х=12
(6+2х)+х=9
6+2х+х=9
3х=15
х=15:3
х=5
Похожие вопросы
Предмет: Другие предметы,
автор: Аноним
Предмет: Физкультура и спорт,
автор: 20apast107
Предмет: Русский язык,
автор: meamka685
Предмет: Физика,
автор: Ленка13
Предмет: Химия,
автор: D43